INTEGRASI ARTIFICIAL INTELLIGENCE DALAM PEMBELAJARAN PENDIDIKAN ISLAM: PELUANG, TANTANGAN, DAN IMPLIKASI PEDAGOGIS - Fauzan, Ahmad; Rizki Maulana; Siti Nur Aisyah (Jurnal Dinamika Pendidikan Islam, 2026)
The rapid development of Artificial Intelligence (AI) opens a new chapter in education, including Islamic education. This study aims to examine the opportunities, challenges, and pedagogical implications of AI integration in Islamic education in Indonesia. Employing a systematic literature review of 48 reputable journal articles published between 2020–2024, supplemented by qualitative field studies at ten Islamic educational institutions. The findings reveal that AI holds great potential for enhancing learning personalization, assessment efficiency, and accessibility of Islamic content. However, ethical, theological, and educator competency challenges remain significant barriers that must be addressed. Pedagogical implications suggest the need to develop an AI-Islamic Pedagogy framework that integrates Islamic values as an ethical foundation for AI use in education. The study concludes that AI integration in Islamic education must be implemented gradually, systematically, and grounded in a robust Islamic epistemology.